Investigating the Effectiveness of Hash Line Baseline for File Integrity Monitoring - Jukuntla, Amar; Gutha, Gayathri; Palem, Annjana; Kotaru, Sri Lakshmi Sowjanya; Alavala, Rajani (2024 5th International Conference on Image Processing and Capsule Networks (ICIPCN), 2024)
This study outlines the value of file integrity and the effective role hashing plays in maintaining it. The goal of the study is to assess how well these techniques make use of PowerShell's capabilities to monitor and protect important files in a system's file manager. It analyses the effectiveness of the Baseline and Hash line in File Integrity Monitoring to see whether the approach can be used to improve file security. This study seeks to provide confidentiality, integrity, and availability to the files as a comprehensive integrity solution for all files in a system simultaneously. The CIA triad is emphasized in the findings as being fundamental to file management. By applying these concepts using PowerShell-based File Integrity Management, this aims to develop a cohesive integrity solution that can simultaneously secure all files on a system. This comprehensive strategy improves complete file security by protecting against internal and external weaknesses. The research discusses how PowerShell-driven FIM techniques might strengthen file security. This provides important insights towards creating comprehensive, reliable solutions for preserving file integrity across several systems by concentrating on the CIA trio.